Expression of MUC1 in esophageal squamous-cell carcinoma and its relationship with prognosis of patients from Linzhou city, a high incidence area of northern China - Song, Zi-Bo (World J Gastroenterol, 2003)
AIM: To further characterize the possible relationship between the molecular changes and prognosis of ESC and to elucidate the possible mechanisms involved. METHODS: 114 specimens of ESC were collected from Linzhou city, and all patients were followed up for more than 5 years after resection. Histopathological analysis and immunohistochemical staining (ABC) were employed to detect the alteration of MUC1. RESULTS: The positive immunostaining rate for MUC1 was 79% (90/114), and the high-expression rate was 63% (72/114). The mean survival periods (months) of those with high- and low-expression rates of MUC1 were 41 (95%CI: 35, 47) and 52 (95%CI: 45, 59), respectively. Patients in the low-expression group obviously survived longer than those in high-expression group, and the difference was significant (P < 0.05). The expression of MUC1 protein in the esophageal carcinoma specimens with metastasis was stronger than those without metastasis, the difference was also significant (P < 0.05). The stepwise multivariate analysis showed that “differentiation”, “expression of MUC1” and “TNM staging” were the most important factors affecting the prognosis of esophageal carcinoma patients (P < 0.05). CONCLUSION: A good correlation between the alteration of MUC1 and the regional lymph node metastasis was observed. Furthermore, high-expression of MUC1 was associated with poor prognosis for esophageal cancer patients. These results indicated that MUC1 is a promising biomarker for predicting lymph node metastasis and prognosis in esophageal cancer.